Conceitos equivocados acerca da COVID-19: como conhecimentos científicos podem contrapor o negacionismo - Deliberalli, João Victor (Universidade Federal de São Carlos, 2023)
In human history there are many records of diseases that took on pandemic proportions. From the bubonic plague in the Middle Ages, to the Spanish flu in the 20th century and the emergence of the new coronavirus in recent years. A mutation that occurred during the replication of the wild coronavirus (SARS-coronavirus), possibly allowed the infection of humans. The disease caused by this modified virus became known as Covid-19 and was responsible for the deaths of more than 6 million people worldwide. Worldwide debates took place about prevention methods and the pandemic brought with it a range of doubts. Much has been discussed about the effectiveness of vaccines that were proven to be ready for use at a remarkable speed due to several studies that were already underway even before this disease became a pandemic. Despite the scientific criticism applied during the development of these vaccines, there was great concern in the general population regarding the safety of using these medications, a fact that was also incited and encouraged by several political leaders. From the wide possibilities of information dissemination in the modern world, it is common to observe the emergence of misconceptions that end up being widely disseminated, a fact defined as “misconceptions”. It is in the midst of this scenario that we find a paradox in which, on the one hand, there is an excess of information available, on the other hand, there are indications of a lack of scientific validation and veracity in the instructions. With this guideline, this work sought to identify common sense notions about the SARS-Cov-2 pandemic and, based on this, propose a didactic sequence that aimed to contribute to overcoming misperceptions about demography and viral biology, using of basic genetics concepts as a teaching strategy in a didactic sequence proposed for the 9th grade of Elementary School. It is considered, therefore, that improving aspects of teaching-learning evolution during basic education can help to overcome conceptual limits commonly observed in the population and contribute to the formation of critical citizens.
Misconceptions about COVID-19: how scientific knowledge can challenge negationism
Keywords: Pandemia; Coronavírus; Negacionismo; Conhecimento Evolutivo; Sequência Didática; Pandemic; Coronavirus; Denialism; Evolutionary Knowledge; Following Teaching; CIENCIAS BIOLOGICAS::GENETICA